A Functional Variant in the Aquaporin-3 Promoter Modulates Its Expression and Correlates With Resistance to Porcine Epidemic Virus Infection in Porcine Intestinal Epithelial Cells - Haifei Wang; Zhenbin Bi; Kaiyu Dai; Pinghua Li; Ruihua Huang; Shenglong Wu; Shenglong Wu; Wenbin Bao; Wenbin Bao (Frontiers in Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) causes a highly contagious intestinal disease in neonatal pigs. Aquaporin-3 (AQP3) plays important roles in maintenance of intestinal barrier function and regulation of immune responses. However, the roles of AQP3 in mediating PEDV infection to host cells and the regulatory mechanisms of AQP3 expression remain poorly understood. Here, we identified one 16 bp (GGGCGGGGTTGCGGGC) insertion mutation in the AQP3 gene promoter in Large White pigs, with the frequencies of 49.3% of heterozygotes and 31.3% of mutant homozygotes. Functional analysis by luciferase activity assay indicated that the insertion mutation results in significant enhancement in AQP3 transcriptional activity (P < 0.01). Mechanistic analysis showed that the inserted sequence adds binding sites for transcription factor CEBPA, which promotes the expression of AQP3. Downregulation of AQP3 by shRNA silencing in porcine intestinal epithelial cells revealed obvious increases in genome copies and viral titers of PEDV. Expression of proinflammatory cytokines (IL-6, IL-8, and IL-18) and interferons (IFN-α and IFN-β) were significantly reduced (P < 0.01) in AQP3 knockdown cells upon PEDV infection. Furthermore, decreased level of ZO-1 protein was also detected in AQP3 knockdown cells in response to PEDV infection. Our findings suggested a previously unknown mechanism linking the effects of promoter genetic variants on the expression of AQP3, revealed the roles of AQP3 in response to PEDV pathogenesis, and indicated the potential associations of the 16 bp insertion mutation with resistance to PEDV infection in porcine intestinal epithelial cells.